Elementos Emancipatórios na Pobreza Multidimensional: A Gestão dos Ativos Intangíveis e do Capital Social (Desenvolvimento em Questão, 2020)
The study aims at a view of poverty in an emancipatory perspective that allows to problematize the conceptions of multidimensional poverty with its core in the discernment and management of intangible assets and social capital. For this purpose, a review of the narrative literature was carried out in the development of this theoretical essay, focusing on poverty, capital, and intangible assets. The content contributes to the multidimensional view of poverty, for which this situation is not based only on the scarcity of income, going beyond what is recommended in traditional economic theory. The theoretical foundations run through the sociological approaches of Sen (2000) and Bourdieu (1986). The result indicates that the relational dimensions are not perceived and applied in the field of Administration, since they work with social capital in the financial and investment aspects. There is a gap to be explored that encompasses conceptual ambiguities, among them, the concept of social capital with an economic and financial focus that leaves out social relations immersed in the origins and mutations of capital. This capitalist view contradicts itself with the sustainability that becomes essential to studies of poverty, or rather, of the poverty to be studied by the Administration field.
Keywords: Poverty. Share capital. Social assets. Intangible Assets. Social management.